BRINGING ANOTHER PERSON TO COURT - Ionuț TIRITEU (Challenges of the Knowledge Society)
This paper analyzes the legal framework applicable to the request for bringing another person into a civil trial, focusing on the essential conditions for submitting such a request and its legal effects within civil proceedings. The paper seeks to provide reasoned solutions to the main issues identified by legal doctrine or observed in case-law regarding the mechanism of bringing another person to court. Bringing another person into a lawsuit can represent a key procedural instrument, as it primarily aims to clarify the legal relationships between the parties involved, in order to prevent contradictory rulings in separate proceedings. Nevertheless, it is not a frequently used tool in judicial practice, which has led to a lack of attention from legal doctrine regarding this type of incidental request. We believe this may also be due to the unclear legal regulation and, consequently, the insufficient understanding of the legal regime applicable to such requests. Therefore, the ultimate goal of this paper is to contribute to encouraging legal practitioners to use this type of forced intervention request more often — an objective that can only be achieved through a solid understanding of the legal framework governing it.